ENDIDIKAN KARAKTER KEAGAMAAN BERBASIS BOARDING SCHOOL SEBAGAI PENUNJANG KEBERHASILAN PENDIDIKAN AKHLAK (Studi Kasus di MTs Al Abror Metro) - andallus jausan; Iswati; heri cahyono (PROFETIK: Jurnal Mahasiswa Pendidikan Agama Islam, 2026)
Andallus Shandy Jausan NPM. 18250002 Thesis: Religious Character Education Based on Boarding Schools as Supporting the Success of Moral Education (Case Study at MTs Al Abror Metro). This thesis was supervised by Iswati, M.Pd.I and Heri Cahyono, M.Pd.I. Character education and the formation of good morals are very important things in the educational process. Because morals and character will later make students have good manners in everyday life. This research aims to determine: 1) The role of boarding schools in supporting the success of students' moral education. 2) Supporting and inhibiting factors for the success of students' moral education and, 3) Boarding school efforts to support the success of students' moral education, at MTs Al Abror Metro based on the moral education program and moral education strategies in the dormitory. This research uses qualitative methods, the data collection techniques use interviews, observation and data collection. Data analysis technique, the author uses the Miles and Huberman model of data analysis which consists of two steps, namely qualitative data analysis before going to the field and qualitative data analysis in the field. The research results show that the dormitory development program is running quite effectively with all the efforts and strategies carried out by all teachers at MTs Al Abror. This can be seen from the cultivation of morals carried out by all MTs Al Abror teachers as well as the strategy carried out, namely integrating the moral education program with daily activities in addition to carrying out programmed activities such as kultum, tahfidz Koran, routine recitation, Lail prayers and etc., although there are several obstacles in implementing moral education, it can be concluded that moral education at the Boarding School is sufficient to support the success of moral education for MTs Al Abror Metro students